P324 How do the psychosocial characteristics of women attending sexual health services differ from those attending primary care?. (14th July 2019) - Edelman, Natalie; Whetham, Jennifer; Gersten, Abi; Mercer, Catherine; Visser, Richard De; Jones, Chris; Bremner, Stephen; Cassell, Jackie
Abstract : Background: Women attending specialist sexual health and contraception clinics (SHAC) are younger and more likely to report substance use and sexual risk behaviours than those attending Primary Care (PC). A broader analysis of psychosocial differences between these populations may improve our understanding of the wider determinants of sexual risk and morbidity and support the development of psychosocial interventions for use in specialist settings. We therefore explored which psychosocial factors were associated with recruitment site. Methods: Psychosocial question responses were compared from a cross-sectional survey of convenience-sampled women aged 16–44 years attending PC (Primary Care) vs SHAC services in the city of Brighton and Hove, UK. Multivariable logistic regression was used to identify which psychosocial factors predicted attendance in SHAC versus PC. Results: 1238 (70%) eligible women completed a questionnaire in a PC setting and 532 (30%) women in a SHAC service. After controlling for age, several psychosocial factors predicted SHAC compared to PC attendance. These included: living in rented accommodation (adjusted odds ratio (aOR)=1.70, 95% confidence interval (CI):1.20–2.40), being a cigarette smoker (aOR=1.32, 95%CI:1.00–1.75), disagreement that 'having a partner at all times is important to me' (aOR=2.24, 95%CI:1.69–2.97) emotional dissatisfaction with most recent relationship (aOR=1.51, 95%CI:1.15–1.99) and little or no functional social support (e.g. help with chores and meals) (aOR=1.83, 95%CI:1.21–2.78). Conclusion: Findings suggest that women attending SHAC may be more likely to experience lack of support and dissatisfaction with sexual and other relationships, and may be more likely to be in rented or other insecure housing compared with those attending primary care settings. Thus, the potential impact of broader life circumstances on sexual risk may be worthy of discussion during clinical and health advisor consultations. Disclosure: No significant relationships.